Morpho-anatomy of in vitro germination and cryopreservation of the orchid Cattleya crispa (Orchidaceae) - Vargas Andriolli, Bruna (2023)
Introduction: Cattleya crispa is an ornamental epiphytic orchid with geographic distribution restricted to the Brazilian Atlantic Forest. Due to predatory extractivism and human-induced habitat loss, this species appears on the Red List of Brazilian Flora. Objective: To characterize morpho-anatomical aspects regarding germination and post-seminal development from C. crispa seeds; as well as studying the effect of cryopreservation on these seeds. Methods: We used light microscopy and electron microscopy to describe the microstructure of a 100 ripe seeds. We evaluated seed viability, seed germination, survival rate and protocorm weight in cryopreserved and non-cryopreserved material, with four replicas per treatment using 20 mg of plant material. Results: The seeds are fusiform, whitish yellow with a length from 700 to 900 µm and a water content of 5 %. Germination began seven days after sowing, the formation of the globular protocorm at 30 days and the formation of the seedling occurred 150 days. The persistent seed coat can compress the protocorm and cause it to collapse. The cryopreserved seeds presented 87.15 % viability, 78.32 % germination, 8.48 % survival and protocorms with 104.27 mg five months after sowing. Data wasn’t different to non-cryopreserved seeds. Conclusions: The cryocapability of the seeds shows that cryopreservation can be used for long-term conservation. The results of this work contribute to the overall biology of C. crispa and to the propagation and storage of genetic material for conservation purposes. Objective: To characterize morpho-anatomical aspects regarding germination and initial development from C. crispa seeds; as well as studying the effect of cryopreservation on these seeds. Methods: Mature capsules of C. crispa were collected from the ex-situ conservation collection of the Orquidário Frederico Carlos Hoehne - Institute of Botany (São Paulo-Brazil). We used light microscopy, scanning electron microscopy and transmission electron microscopy. Seed viability (%), seed germination (%), survival rate (%) and protocorms weight (mg) were evaluated. Results: Our analyses showed that the globular embryo has a homogeneously early germination that occurs by the 7th day. The germinating protocorm shows bipolarity, with shoot apex and basal region. The embryo is composed mostly of lipid and protein bodies and contains a few small grains of starch. Scanning electron microscopy images revealed a persistent seed coat that does not influence the onset of germination, however, can compress the protocorm and lead to its collapse. The initial water content of the seeds was 5 %. Seeds submitted to cryopreservation resulted in a high germination rate (81.14 %). However, the survival rate of non-cryopreserved (8.48 %) and cryopreserved (11.12 %) protocorms, evaluated five months after sowing, was reduced. Conclusions: The cryocapability of the seeds shows that cryopreservation can be used for long-term conservation. The results of this work contribute to the overall biology of C. crispa and to the propagation and storage of genetic material for conservation purposes.